2020
DOI: 10.1242/jcs.246637
|View full text |Cite
|
Sign up to set email alerts
|

The single flagellum of Leishmania has a fixed polarisation of its asymmetric beat

Abstract: Eukaryotic flagella undertake different beat types as necessary for different functions; for example, the Leishmania parasite flagellum undergoes a symmetric tip-to-base beat for forward swimming and an asymmetric base-to-tip beat to rotate the cell. In multi-ciliated tissues or organisms, the asymmetric beats are coordinated, leading to movement of the cell, organism or surrounding fluid. This coordination involves a polarisation of power stroke direction. Here, we asked whether the asymmetric beat of the sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
(93 reference statements)
0
14
0
1
Order By: Relevance
“…Because the net effect on TbLC2 knockdown cells is a decrease in their directional motility persistence ( Fig 6D and 6E ), these results further support the conclusion that asymmetry of the beating waveform is the dominant effect of TbLC2 knockdown on swimming motility. Moreover, that the reverse base-to-tip ciliary beating mode in wild-type and TbLC2 knockdown trypanosomes is more asymmetric than the forward tip-to-base beating mode [ 22 , 68 ] ( Fig 7A and 7B as compared to S9 and S10 Figs) provides additional support for the conclusion that the asymmetry of the base-to-tip ciliary beat waveform dominates the tumbling mechanism, rather than the base-to-tip waveform propagation direction, itself.…”
Section: Discussionmentioning
confidence: 99%
“…Because the net effect on TbLC2 knockdown cells is a decrease in their directional motility persistence ( Fig 6D and 6E ), these results further support the conclusion that asymmetry of the beating waveform is the dominant effect of TbLC2 knockdown on swimming motility. Moreover, that the reverse base-to-tip ciliary beating mode in wild-type and TbLC2 knockdown trypanosomes is more asymmetric than the forward tip-to-base beating mode [ 22 , 68 ] ( Fig 7A and 7B as compared to S9 and S10 Figs) provides additional support for the conclusion that the asymmetry of the base-to-tip ciliary beat waveform dominates the tumbling mechanism, rather than the base-to-tip waveform propagation direction, itself.…”
Section: Discussionmentioning
confidence: 99%
“…The PF16 gene was chosen as a target to test the CRISPR/Cas9 system in Lb C9/T7 since its complete deletion causes a well-characterized and easily detected phenotype of paralysis in Leishmania ( Beneke et al., 2017 ). Besides, PF16, which is distributed all over the flagella and flagellar pocket, can be tagged with reporter proteins such as mNG and eYFP ( Beneke et al., 2017 ; Dean et al., 2017 ; Wang et al., 2020 ). In the strategy developed by Beneke and Gluenz (2019) , two donor cassettes with two different resistance markers are delivered to the cell to mediate DSB repair, resulting in the complete and uniform deletion of CDS without the need for cloning.…”
Section: Discussionmentioning
confidence: 99%
“…Our electron microscopy showed that, despite being much reduced, the haptomonad axoneme still contained some of the canonical non-microtubule components such as the radial spokes, while the PFR was absent (Figure 2E). To examine this at the molecular level, we differentiated a cell line expressing a radial spoke protein (RSP4/6) tagged with mScarlet and a PFR protein (PFR2) tagged with mNeonGreen (mNG; Wang et al, 2021), and examined the differentiating cells by fluorescence light microscopy (Figure 4D). In promastigote cells, RSP4/6 and PFR2 had their expected localisations along the flagellum.…”
Section: Haptomonad Differentiation Occurs Through a Series Of Define...mentioning
confidence: 99%